Ökonomien der Parodie am Wiener Vorstadttheater Unterhaltungsdramatik in politischen und sozioökonomischen Krisenzeiten - Mansky, Matthias (2022)
Differing from previous research approaches, the parodies of the Viennese popular theatres can be considered as a genre of theatre practice which allows to demonstrate the conditions of production for playwrights in the early 19th century. The book comprises a study and a critical edition of a selective corpus of popular theatre parodies.